The Influence Of Service Quality On Sales Increase At The Maju Teti Store In Gunungsitoli City - Telaumbanua, Otolius; Harefa, Idarni; Zai, Kurniawan Sarototonafo; Gulo, Heniwati (Universitas Dehasen Bengkulu, 2025)
This study aims to determine the influence of service quality on increasing sales at Toko Maju Teti, Gunungsitoli City. The method used in this study is a quantitative method with a total of 62 respondents who shop at Toko Maju Teti, Gunungsitoli City, which was selected using the propability sampling technique using the slovin formula. Data was collected by observation method and distribution of questionnaires directly at Toko Maju Teti, Gunungsitoli City. The results of this study show that based on the results of the partial test (t-test) the t-table value is 10.406 and the t-table is 1.999 which means that t is greater than t table, and the significance value is 0.000 smaller than 0.05 so that it is concluded that the quality of service has an influence on the increase in sales at Toko Maju Teti, Gunungsitoli City. Based on the determinant coefficient test, the results were obtained that the quality of service had an influence on the increase in sales at Toko Maju Teti Kota Gunungsitoli by 64% and 36% was influenced by other factors.